ANALYSIS OF CRITICAL THINKING SKILLS FOR BIOLOGY TEACHER PROSPECTIVE AT UNIVERSITY OF PAPUA - Iwan Iwan; Sutiman Bambang Sumitro; Ibrohim Ibrohim; Fatchur Rohman (JURNAL EDUSCIENCE, 2023)
This research is a type of descriptive research with the aim of knowing the critical thinking ability profile of prospective biology teachers at the University of Papua. The population in this study were all prospective biology teacher students at the University of Papua. The sampling technique is purposive sampling, namely sampling based on a specific purpose. The number of respondents was 42 prospective biology teachers. The instrument is in the form of essay questions. Based on research data analysis, the average proportion of critical thinking skills for biology teacher candidates is 55.03. Furthermore, the proportions based on critical thinking criteria are 10% uncritical, 53.33% less critical, 36.67% critical and 2.38% very critical. This in general it can be interpreted that the critical thinking skills of prospective biology teachers at the University of Papua are in the less critical category, this is very important to be empowered as a provision to face competition in the era of the industrial revolution 4.0.Keywords: Analysis, Critical Thinking Skills, Prospective Biology TeachersAbstrak Penelitian ini merupakan jenis penelitian deskriptif dengan tujuan untuk mengetahui profil kemampuan berpikir kritis calon guru biologi di Universitas Papua. Populasi dalam penelitian ini adalah seluruh mahasiswa calon guru biologi di Universitas Papua. Teknik pengambilan sampel dengan cara Purposive Sampling yakni pengambilan sampel berdasarkan tujuan tertentu. Jumlah responden sebanyak 42 calon guru biologi. Instrumen berupa soal essay. Berdasarkan  analisis data hasil penelitian  rata-rata persentase  keterampilan berpikir kritis calon guru biologi yaitu 55,03. Selanjutnya persentase berdasarkan kriteria berpikir kritis yaitu  kategori tidak kritis 10%, kurang kritis 53,33%, kritis 36,67 % dan sangat kritis 2,38%. Dengan demikian secara umum dapat disimpulkan bahwa keterampilan berpikir kritis calon guru biologi Universitas Papua berada pada kategori kurang kritis, hal ini kiranya sangat penting  untuk diberdayakan sebagai bekal untuk menghadapi persaingan di era revolusi industry 4.0.Kata Kunci:  Analisis, Keterampilan Berpikir Kritis, Calon Guru Biologi